10x-5=6x+11

Simple and best practice solution for 10x-5=6x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-5=6x+11 equation:


Simplifying
10x + -5 = 6x + 11

Reorder the terms:
-5 + 10x = 6x + 11

Reorder the terms:
-5 + 10x = 11 + 6x

Solving
-5 + 10x = 11 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-5 + 10x + -6x = 11 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-5 + 4x = 11 + 6x + -6x

Combine like terms: 6x + -6x = 0
-5 + 4x = 11 + 0
-5 + 4x = 11

Add '5' to each side of the equation.
-5 + 5 + 4x = 11 + 5

Combine like terms: -5 + 5 = 0
0 + 4x = 11 + 5
4x = 11 + 5

Combine like terms: 11 + 5 = 16
4x = 16

Divide each side by '4'.
x = 4

Simplifying
x = 4

See similar equations:

| 12y-8+4y+y= | | 3b+4=2b-4 | | 3x+4x=-39 | | 7x+4=7x+4 | | x-10=-10 | | 5m=37-3 | | 16x+12=8x+48 | | 6(x-3)+66=-2x | | -x=0.73 | | (x-1)=-4x+24 | | 8x-6=2x+18 | | -7(2b+4)+(15b-6)=0 | | 8x+5=37 | | t-5-2t+5= | | 30x+21=-45x-10 | | x^2=5y^2-25y+60 | | 3h-5=-8(6+5h) | | 2x=-3x+10 | | 8x+18=-26+8x | | 3(x-1)+43=-2x | | x-154=-7+86 | | (7-3x)*x=40 | | 19-0.25x+2-x=2 | | 8b+6-8b+1= | | 8x+t-4=0 | | 11x^2=1+9x | | 4(x-2)=-4x+56 | | 3x+1=x-3 | | (7-3x)x=40 | | 9x-3=2x+18 | | -44+2x=-x+40 | | 5x^2=23x+6 |

Equations solver categories